Evaluation of Manganese (Mn) and Cadmium (Cd) Heavy Metal Content in Staple Foods Based on Food Sources and Environmental Conditions in Pregnant Women in Sambas Regency, Indonesia - Taufik Anwar; Slamet; Supriyanto; Cecep Dani Sucipto; Suharno (Gema Lingkungan Kesehatan, 2025)
Exposure to heavy metals, particularly Manganese (Mn) and Cadmium (Cd), in staple foods is a serious health issue for pregnant women in Sambas Regency, Indonesia. This study aims to evaluate the content of Mn and Cd in staple foods and environmental factors that influence exposure in pregnant women. The method used was an analytical observational design with a cross-sectional approach, involving 93 pregnant women selected by purposive sampling. Data were collected through structured interviews and laboratory analysis using atomic absorption spectrometry. The results showed that the average level of Mn in rice was 7.37 mg/kg, while the average level of Cd was 0.056 mg/kg. A total of 68.8% of respondents obtained their rice from local markets, potentially increasing the risk of heavy metal exposure. In addition, 87.1% of respondents reported using house paint, which could be an additional source of exposure. Conclusions from this study emphasise the need for closer monitoring of food quality and education on the dangers of heavy metal exposure for pregnant women, as well as the need for further research to understand the cumulative impact of multi-metal exposure in the context of pregnancy.